Polityka podatkowa nazistowskich Niemiec — zarys problematyki - Lipniewicz, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Taxes constitute an integral part of the state economic policy, regardless of the political system or dominant ideology. It is therefore not surprising that they were an essential tool for achieving the goals of Nazi Germany, of both fiscal and non-fiscal nature. The purpose of the paper is to examine in scientific terms the issues of (i) the use of taxes by the governments of Nazi Germany to increase budget revenues necessary to achieve political and military goals, as well as (ii) the Nazis’ recognition of public levies as a form of specific economic oppression serving the implementation of the state’s policy towards the Jewish population in Germany.
Keywords: system podatkowy; nazistowskie Niemcy; podatek konfiskacyjny; budżet